Cost Optimizing in Interventional Ozone Spine Therapy - Omidi Varmezani, Reza (Digital Repository of Theses - SSBM Geneva, 2024)
Back pain is cost-intensive, as it is often the reason for sick leave and causes high direct and indirect costs. There are no comprehensive and meaningful studies that perform a cost-benefit analysis between MRI-guided and CT-guided interventional spinal O3 nucleolysis from both a medical and economic perspective. This study used a qualitative case method to provide insights into a problem and help develop hypotheses by calculation the real costs of MRguided and CT-guided O3 interventional spinal neucleolysis. This module must take into account all variable and constant variants (acquisition costs, personnel costs, maintenance costs, etc.) and long term costs because of radiotaion exposure. In this study is the average intervention time for MRI guided interventions was 24.9 ± 6.3 minutes (range: 17 – 36 minutes). Preinterventional patient preparation took an average of 22 minutes, while postinterventional activities took an average of 9 minutes. A CT guided intervention took an average of 19.7 ± 7.9 minutes (range: 5 – 54 minutes) with an average of 20 minutes of preinterventional preparation and 9 minutes of postinterventional activities. The approximated average effective dose for CT-guided interventions was 0.48 ± 0.51 mSv (range: 0.07 – 1.92 mSv). Mean intervention time was 70.8 min (48–90 min) for MR-guided and 60.4 min (52–75 min) for CT-guided treatment. The average total costs per patient were CHF 290.29 for MRguided and CHF 175.46 for CT-guided interventions. These consisted of (MR/CT guidance) CHF 72/29 for equipment use, CHF 99.47/84.84 for staff and CHF 118.55/61.95 for disposables. Intradiskal Nucleolysis with O3 using MRI guidance is more expensive as using CT guidance. Given the advantages of no radiation exposure and possible future decrease in prices for MRI devices, MR-guided spinal interventions may become a promising alternative to the CT-guided procedure.